Calcium metabolism in sarcoidosis. Issue 538 (August 1970) - Dent, C. E.
Abstract : Fifteen patients with hypercalcaemia and sarcoidosis have been studied. Twelve were males of average age 34; the three females averaged 53. Cases included widely varying sarcoid manifestations, but five gave a clear history of rather excessive ingestion of low-dosage vitamin D preparations. The data confirm that in most cases there is an undue sensitivity to all the actions of vitamin D, the situation therefore mimicking vitamin D intoxication. Two patients volunteered to receive ultra-violet irradiation and became hypercalcaemic with corresponding clinical and biochemical changes. Steroids make normal the calcium abnormalities just as they do in straight vitamin D intoxication. However, in three further patients the hypercalcaemia did not respond to steroids and was shown to be due to the presence of an over-acting parathyroid gland, removal of which corrected the abnormality. There are a sufficient number of other similar cases in the literature to suggest that the development of parathyroid adenomas is another even rarer complication of sarcoidosis which must be carefully distinguished from vitamin D sensitivity.